2020
DOI: 10.1111/1467-9566.13154
|View full text |Cite
|
Sign up to set email alerts
|

Risk work in dental practices: an ethnographic study of how risk is managed in NHS dental appointments

Abstract: Ideas about disease risk underpin many preventive health strategies. These have assumed even greater importance in recent years as health policies place a growing emphasis on personal responsibility. This is reflected in new national contracts for National Health Service (NHS) dentistry that emphasise informing patients on their oral health risk status to persuade them to be accountable for their health. Thus, 'risk' is now central to the practice of dentistry, particularly primary care delivery. An ethnograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…An ethnographic study of risk work in GDP has found that the process of consent requires getting patients to accept risks and take responsibility to make a decision [39]. Lack of previous relationship with patients in OOH together with lack of access to patient medical records contributed to additional pressure on time when gaining valid consent [40] before dental procedures in OOH.…”
Section: Discussionmentioning
confidence: 99%
“…An ethnographic study of risk work in GDP has found that the process of consent requires getting patients to accept risks and take responsibility to make a decision [39]. Lack of previous relationship with patients in OOH together with lack of access to patient medical records contributed to additional pressure on time when gaining valid consent [40] before dental procedures in OOH.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, accurately determining the cost of defensive medicine can be complex, as its computation occasionally approximates the entire healthcare wastage, of which defensive practices represent just one facet [ 38 ]. Nonetheless, more recent research has proposed that the comprehensive expense associated with defensive practices spans from $46 billion to $300 billion, with most estimates falling within the $50 to $65 billion bracket [ 15 , 39 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent ethnographic study in the North of England examined how risk is acted on in primary care dental settings. 2 They found that the everyday nature of risk work in NHS dental practices is often implicit, defensive, and focused on social interaction rather than explicit discussions of individual lifestyle risks that policymakers assume. Sounds familiar.…”
mentioning
confidence: 99%